RETURN ON INVESTMENT FROM SHOPPING CENTRES GALLERIA STARA ZAGORA AND BURGAS PLAZA, BULGARIA: RETURN ON INVESTMENT FROM SHOPPING CENTRES GALLERIA STARA ZAGORA AND BURGAS PLAZA, BULGARIA - Ivanov, Ivaylo (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
The topic of return on investment is of extreme importance and the one determining the building and the development of every shopping centre. This article reviews two malls in Bulgaria, each with its own peculiarities and advantages. The information comes from the official financial reports of the companies. It is crucial to bear in mind that the models of funding, building and rental rates of both centres were prepared in the years before the financial crisis of 2008. For that reason, the returns on the investment rate negative.